Optical properties of 2D GeTe under strain: A DFT study - O. Ruiz-Cigarrillo; G. Flores-Rangel; U. Zavala-Moran; J. Puebla; R. E. Balderas-Navarro; B. Mizaikoff (AIP Advances)
Monolayer germanium telluride (GeTe) exhibits tunable electronic and optical properties, making it promising for device applications. Using Density Functional Theory (DFT), we investigate the impact of uniaxial strain, ϵ, on its band structure and dielectric function (DF), ε̃. Tensile strain along the —zigzag direction induces a direct-to-indirect bandgap transition at ϵ = 2%, reducing the gap from 1.80 to 1.62 eV. Compressive strain narrows the gap while maintaining its indirect nature. Strain also induces in-plane anisotropy in the DF and shifts the optical absorption spectrum. We determine a deformation potential (DP) of −6.45 eV for the bandgap under tensile strain and DPs for other above bandgap high-symmetry points. These findings highlight the potential of strain engineering for tuning GeTe’s properties in devices.